SISTEM INFORMASI PEMESANAN TIKET PADA PO TRANEX GRAHA MANDIRI PADANG: TICKET ORDERING INFORMATION SYSTEM AT PO TRANEX GRAHA MANDIRI PADANG - A Siregar, M Ilham; Adila, Sonia (JENTIK, 2024)
Bus is one of the most widely used means of transportation by the public because the price is affordabable for the lower middle class. In the service of purchasing bus tickets in PO Tranex Padang city is done by going directly to the PO or call to the agen oon duty.this kind of booking process has shortcomings where employees are hassles in recording and often errors occur in recording tiket reservations. This study aims to design a ticket purchasing system to facilitate the leadership of employees and passengers in the management of bus tickets. Metodology used in the manufacture of this system is using the SDLC method, namely ; planning the creaction of aplictions, analysis that is collecting needs ind infomation in the manufacture os systems, system design that is designing softwere architecture and interface representation, design that is designing the stucture and appearance of the aplication, as well as application tials conducted by computers with windows 10 operating system. Hopefully this application can help user in making ticket sales transction